The determinants of economic growth in developed countries: case in United States / Khairunnisha Abd Malek - Abd Malek, Khairunnisha (Faculty of Business and Management, 2018)
Economic growth is a standout among the most imperative indicators of a solid economy. Increase in GDP implies higher profitability, which prompts more individuals being employed. Consequently, all nations need positive economic growth. This makes economic growth the most analysed economic indicator. Although economic growth is important to the economy, there are certain issues that can affect economic growth which are inflation rate, foreign direct investment and remittances that should still be taken into consideration. Thus, a further research and study is needed to examine and identify more about these factors. This research aim is to determine which of these three factors that actually played an important role towards economic growth in developed country of United States. This research is based on data obtained from World Bank Indicators and the data for this study are analysed based on time series data. The sample consists of 35 observations from 1982 until 2016. The data was analysed to evaluate and determine which factors that influence economic growth successfully. It is hope that the study can contribute to the improvement of economic growth in United States and be a great sample to other countries.